Productivity effects of international outsourcing: Evidence from plant level data - Holger Görg; Aoife Hanley; Eric Strobl (Centre for Economic Policy Research (CEPR), 2007)
We investigate the impact of international outsourcing on productivity using plant level data for Irish manufacturing. Specifically, we distinguish the effect of outsourcing of materials from services inputs. Moreover, we examine whether the impact on productivity is different for plants being more embedded in international markets through exporting or being part of a multinational. Our results show robust evidence for positive effects from outsourcing of services inputs for exporters, either domestic- or foreignowned. By contrast, we find no statistically significant evidence of an impact of international outsourcing of services on productivity for firms not operating on the export market.
Keywords: F14; F23; L23; 330; Multinationales Unternehmen; Auslandsniederlassung; Export; Outsourcing; Dienstleistung; Produktivität; Irland